Characterizing the landscape of cervical squamous cell carcinoma immune microenvironment by integrating the single‐cell transcriptomics and RNA‐Seq. Issue 6 (11th May 2022) - Yin, Ruiling; Zhai, Xiuming; Han, Hongyan; Tong, Xuedong; Li, Yan; Deng, Kun
Abstract: Background: Cervical squamous cell carcinoma (CSCC), caused by the infection of high‐risk human papillomavirus, is one of the most common malignancies in women worldwide. Methods: RNA expression data, including those from the Cancer Genome Atlas, Gene Expression Omnibus, and Genotype‐Tissue Expression databases, were used to identify the expression of RNAs in normal and tumor tissue. Correlation analysis was performed to identify the immune‐related long noncoding RNAs (IRLs) and hypoxia‐related genes (IRHs) that can influence the activity of the immune system. Prognosis models of immune‐related RNAs (IRRs) were used to construct a coexpression network of the immune system. We identified the role of IRRs in immunotherapy by correlation analysis with immune checkpoint genes (ICGs). We then validated the expression data by integrating two single‐cell sequencing data sets of CSCC to identify the key immune features. Results: In total, six immune‐related gene (IRG), four IRL, and five IRH signatures that can significantly influence the characteristics of the tumor immune microenvironment (TIME) were selected using machine learning methods. The expression level of ICGs was significantly upregulated in GZMB + CD8 + T‐cells and tumor‐associated macrophages (TAMs) in tumor tissues. TGFBI + TAMs are a kind of blood‐derived monocyte‐derived M0‐like TAM linked to hypoxia and a poor prognosis. IFI30 + M1‐like TAMs participate in the process of immune‐regulation and showed a role in the promotion of CD8 + T‐cells and Type 1 T helper (Th1)/Th2 cells in the coexpression network, together with several IRLs, IRGs, and ICGs. Conclusions: CD16 + monocyte‐derived IFI30 + TAMs participated in our coexpression network to regulate the TIME, showing the potential to be a novel immunotherapy target. The enrichment of M0‐like TAMs was associated with a worse prognosis in the high‐risk score group with IRH signatures. Remarkably, M0‐like TAMs in tumor tissues overexpressed TGFBI and were associated with several well‐known tumor‐proliferation pathways. Abstract : Cervical squamous cells carcinoma (CESC), caused by the infection of high‐risk human papillomavirus (HR‐HPV). We investigate a combination of multiple immune biomarkers as a clinically signature that can predict prognosis, diagnosis, relapse, and therapy in CESC patients.